Mating plan for G3 for Oreochromis andersonii GIP Zambia - Mengistu, Samuel; Hamilton, Matthew (2025)
WorldFish in partnership with the Zambian government has been implementing a GIP at a research station in Kitwe. The research has generated 3 families. This dataset is generation three family production mating list.